دور فرط التوتر الشرياني في الأمراض القلبية الوعائية - أحمد, هدى (Latakia University Journal -Medical Sciences Series, 2014)
إن ارتفاع التوتر الشرياني مرض شائع له اختلاطات قلبية عديدة تعتبر كمصادر للوفيات والمراضة. حددت هذه الاختلاطات بواسطة صورة الصدر وتخطيط القلب الكهربائي ومخطط صدى القلب «الأيكو». تمت هذه الدراسة على 248 مريضاً منهم 140 ذكراً و108 أنثى تراوحت أعمارهم بين 34 ـ 80 سنة. أظهرت دراستنا الاختلاطات القلبية التالية: 1ـ اضطراب الوظيفة الانبساطية 71% 2ـ اعتلال عضلة قلبية ضخامي 43.5% 3 ـ اعتلال عضلة قلبية توسعي 25.8% 4 ـ اضطرابات نظم 29.8% 5 ـ أمراض الشرايين الأكليلية 22.8% أظهرت دراسة العلاقة بين الاختلاطات القلبية والعلاج أن العلاج الكافي والمنتظم ينقص هذه الاختلاطات لدى مرضى ارتفاع التوتر الشرياني. Hypertension is a common disease whose cardiac complications are very important sources of morbidity and mortality. These complications were detected by xray, electra car diography and echo cardiogeaphy. We have 248 patients in our study: 140 male and 108 female whose ages range between 34 and 80. Our study shows that the common cardiac compliations are: disorder of diastolic function (71%). Diloted cardio my opathy25.8%. Hy pertrophic cordiomiopathy.43.5%. arrhythamias (29.8%). coronary arteries disease «22.6%». Studying the relationship between cardiac complications and treatment shows that the regular and sufficient treatment seduces the cardiac compilation of hyprtension.